AB0316 Patient's global assessment of general health by vas at baseline predicts ACR/EULAR remission after 3, 6 and 12 month's of efficient treatment in DMARD- and steroid naÏve early rheumatoid arthritis patients. The danish cimestra-study. (23rd January 2014) - Herly, M.; Stengaard-Pedersen, K.; Vestergaard, P.; Pødenphandt, J.; Østergaard, M.; Junker, P.; Hetland, M.L.; Hørslev-Petersen, K.; Ellingsen, T.
Abstract : Background: At the time of diagnosis, easy-to-use and cost-effective predictors of remission are needed in rheumatoid arthritis (RA) to improve patient care. Objectives: During one year of efficient treatment aiming for remission (1) in 160 DMARD- and steroid naive early RA patients we investigated at baseline how total D-vitamin plasma levels (Dtot), ACPA-status, IgM-RF, CRP, total Sharp score at baseline (TSS0), HAQ, patient's general health assessment (VAS), DAS28 (CRP) at baseline, number of swollen joints (NSJ) and number of tender joints (NTJ), never smoking, age and gender could predict remission, defined by the new ACR/EULAR remission criterias (2) or DAS28 <2.6. Methods: In a multivariate logistic regression model, using backward stepwise selection, baseline values of Dtot, ACPA-status, IgM-RF, CRP, TSS0, HAQ, patient's general health assessment VAS, DAS28, NSJ and NTJ, age, never smoking and gender, were evaluated as possible predictors of ACR/EULAR remission and DAS28 <2, 6 after 3, 6 and 12 months of treatment, p<0.05 was considered significant. Results: At 3 months: ACR/EULAR remission was predicted by patient's general health assessment (p<0.001). DAS28 <2.6 was predicted by patient's general health assessment (p=0.024), ACPA (p=0.08), IgM-RF (p=0.028), gender (p=0.028), DAS28 baseline (p<0.001) and NTJ (p=0.002). At 6 months: ACR/EULAR remission was predicted by patient's general health assessment (p=0.036) and DAS28 baseline (p=0.023). DAS28 <2.6 was predicted by DAS28 baseline (p<0.001) and NSJ (p=0.036). At 12 months: ACR/EULAR remission was predicted by patient's general health assessment (p=0.025) and TSS0 (p=0.048). DAS28 <2.6 was predicted by NTJ (p=0.014) Conclusions: In DMARD- and steroid naive early RA patients, the baseline patient's general health assessment predicted ACR/EULAR remission at 3, 6 and 12 month in a multivariate logistic regression analysis. DAS28, NTJ, ACPA, IgM-RF, gender, TSS0 and NSJ predicted remission at 3, 6 or 12 months with less concistency. Dtot did not predict treatment response. References: Hetland, M. L., et al. Combination treatment with methotrexate, cyclosporine, and intraarticular betamethasone compared with methotrexate and intraarticular betamethasone in early active rheumatoid arthritis: an investigator-initiated, multicenter, randomized, double-blind, parallel-group, placebo-controlled study. Arthritis Rheum 54.5 (2006): 1401-09. Felson, D. T., et al. American College of Rheumatology/European League Against Rheumatism provisional definition of remission in rheumatoid arthritis for clinical trials. Arthritis Rheum 63.3 (2011): 573-86. Disclosure of Interest: None Declared